Effectiveness of the Integrated Rehabilitation Program Based on Vibroacoustics and Virtual Reality on the Visual Processing of Children with Autism: Treatment Reports of Five Patients - Narges Amini Shirazi; Saeed Rezayi; Maryam Asaseh; Mohammad Parsa Azizi (مجله دانشگاه علوم پزشکی گرگان, 2023)
The visual processing disorder is broadly observed among individuals with autism. This study was conducted to develop an integrated rehabilitation program based on vibroacoustics and virtual reality and to assess its effectiveness on the visual processing of autistic children. This experimental case report was conducted using an Aberrant Behavior Checklist (ABC) design on 5 children with autism referred to Zehnara Rehabilitation Clinic in the second half months of 2021. First, the integrated program was implemented for ten 30-minute sessions on 2 subjects randomly selected from among the samples. After determining the program validity, 3 more subjects were entered into the study. The sensory profile questionnaire-2 was used. The questionnaires were filled out at the baseline stage, at the end of each intervention session, and at the one-month follow-up stage. The visual analysis, the percentage of recovery, the percentage of non-overlapping data (PND), and the percentage of overlapping data (POD) were used for data analysis. The implemented intervention was evaluated to be effective for all five subjects so that for Subjects No. 1, 2, 3, 4, and 5, the PND rates were obtained to be 90%, 90%, 70%, 100%, and 90%, respectively. The results of this study demonstrated that the integrated sensory rehabilitation program could be used to improve the visual processing of children with autism.